Pendekatan Etnosains dalam Pendidikan Fisika: Meningkatkan Pemahaman Konsep melalui Tradisi Lokal Lompat Batu Nias - Mayang Dela Kesumah; Bambang Hariyadi; Haerul Pathoni; Muhammad Haris Effendi Hasibuan (Pusat Riset dan Inovasi Nasional, 2025)
Physics education is not only aimed at conveying abstract scientific concepts to students, but also to foster an understanding that science is rooted in and relevant to everyday life. One approach that can bridge physics education and everyday life is the ethnoscience approach. The ethnoscience approach in education is a strategy for creating a learning environment and designing learning experiences that integrate culture into learning. This study aims to examine the values ​​of physics in the Nias Stone Jump tradition as an opportunity for physics learning media for students at the secondary school level. By using descriptive qualitative methods and narrative literature review analysis, this study identified various journals and papers that show that local traditions in learning. The results of this study indicate that the Nias Stone Jump tradition has the potential to be an effective learning media to improve students' understanding of physics concepts and analysis in the learning process.